Factors Associated with Incomplete Informed Consent in Inpatient Medical Records - Rudy Dwi Laksono; Mila Sari (Research and Evidence on Knowledge in Administration and Management — Medical Electronic Data and Information Systems, 2026)
Informed consent is a crucial component of medical records that serves as legal evidence and a means of protecting patient rights; however, incomplete documentation remains a common issue that may compromise healthcare quality. This study aimed to analyze factors associated with incomplete informed consent documentation in inpatient medical records. A quantitative study with a cross-sectional design was conducted on 120 medical records selected using systematic random sampling. The dependent variable was the completeness of informed consent, while the independent variables included staff knowledge, years of experience, workload, and compliance with standard operating procedures (SOPs). Data were collected using a checklist based on Ministry of Health Regulation No. 290 of 2008 and analyzed using univariate and bivariate methods with the Chi-square test at a significance level of 0.05. The results showed that incomplete informed consent documentation was relatively high (62.5%). Bivariate analysis indicated that knowledge (p=0.002; OR=5.5), workload (p=0.004; OR=5.0), and SOP compliance (p=0.001; OR=7.55) were significantly associated with incomplete documentation, while years of experience was not significantly associated (p=0.087). In conclusion, the incompleteness of informed consent is influenced by both individual and system-related factors, with SOP compliance identified as the most dominant factor.